Observations on Flowering and Fruiting in Balanites Roxburghii Pl. - Amalraj, V. A. (Indian Forester, 1985)
The information of age at which the plant starts flowering hitherto lacking, is now known. Although flowering is twice in a year, fruits generally are available only once annually during winter. Irregular bearing is observed in some trees. Heredity and vigour are perhaps the factors affecting the bearing. Fruits borne on older and thicker branches usually attain maturity, while premature fruit drop occurs on comparatively younger and thinner branches. Heavy fruit drop has been observed. Both fruit pulp and seed are often infected by two different moth pests.